EFEKTIVITAS PEMBELAJARAN SAINS BERBASIS PROYEK STEM DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA ASPEK DEDUKSI SISWA SMP - Pratiwi, Febriana; Zulirfan, Zulirfan; Yennita, Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The demands of the 21st century that require generations to have the skills needed for a more complex life and work environment are focused on critical thinking, communication, creativity and collaboration skills. The current Covid-19 pandemic has resulted in a change in the process of teaching and learning activities from face-to-face to online. During the online learning period, activities in the classroom or school laboratory are very limited. However, because learning activities must continue, science learning alternatives are carried out through project-based learning using STEM kits so that students can still carry out home experiments in online learning under teacher monitoring digitally through LMS. The purpose of this research was to determine the effectiveness of STEM project-based science learning to improve critical thinking skills in online junior high school students especially at the deduction aspects. This study uses a quasi-experimental type of research with a non-equivalent pretest-posttest control group design. The samples taken are the experimental group and the control group from a population of 3 classes. The class that was given treatment with project-based learning used the STEM project kit that called by the experimental group and the control group was given conventional learning. Research data were collected by giving critical thinking skills tests before learning was carried out (pretest) and after learning the simple aircraft material was completed (posttest) using research instruments in the form of critical thinking skills test questions on the deductive aspect.Keywords: Science Learning Based On STEM Projects, Critical Thinking skills, Deduction Aspect